Impact of sustained professional development in STEM on outcome measures in a diverse urban district. Issue 2 (3rd March 2016) - Capraro, Robert M.; Capraro, Mary Margaret; Scheurich, James Joseph; Jones, Meredith; Morgan, Jim; Huggins, Kristin Shawn; Corlu, M. Sencer; Younes, Rayya; Han, Sunyoung
ABSTRACT: Sustained professional development can support STEM (Science, Technology, Engineering, and Mathematics) reform. The authors describe a 3-year study of sustained professional development for 3 diverse urban schools across the salient factors of fidelity of implementation of project-based learning, development of professional learning communities, and student achievement. Qualitative and quantitative data were collected. The students who experienced the greatest fidelity of implementation exhibited the greatest gains ( d = 1.41–2.03) on standardized test scores, while those with the lowest fidelity of implementation exhibited negative gains ( d = –0.16 to –0.08). Qualitative data indicated teachers perceived there were multiple benefits from the implementation of project-based learning.